Indigenous Peoples of the Russian North and Cold War Ideology - Bartels, Dennis; Bartels, Alice L. (Anthropologica, 2022)
During the Soviet period, much of Western scholar ship on the smaller indigenous groups of the Russian north and far east—that is Northern Peoples—was shaped by Cold War ideology. In this paper, the ways in which Cold War ideology distorted representations of Soviet policy toward Northern Peoples, and some of the consequences of these distortions, are analyzed.